Theory of international economics - Abhishek Sharma (Jaipur Horizon Press, 2020)
Economics and the world; multinational corporation; the development of the GATTWTO system; the uruguay round and beyond; export and import financing; globalization and anti globalization; cross border merger and acquisition.
Keywords: International Economics